(untitled) (Altre Modernità, 2016)
The right to education in Brazil is part of the challenges that have been highlighted in the tensions and conflicts that have lived students and educators to practices and educational policies as a multicultural locus. Therefore, those who have been categorized as ’minorities’ throughout history and, following that, did not take part in public policy, modern origin, have developed important role in contemporary social change towards inclusion in educational practices of the diversity of these ethnic-cultural groups.